Desenvolvimento e comparação de células solares bifaciais processadas com redução de etapas térmicas em lâminas de silício com diferentes resistividades de base - Kochenborger, Augusto dos Santos (2021)
In the global market of solar cells, there is a trend to increase the commercialization of PERC and bifacial devices. The objective of this work is to develop p-type bifacial solar cell with PERT structure, produced with the diffusion of dopants in the same thermal step on substrates with different base resistivity. For this, the boron back suface field was experimentally optimized and the sheet resistance, electrical parameters, bifaciality and internal quantum efficiency of bifacial solar cells, produced with boron diffusion temperature (TB) from 940 °C to 970 °C in substrates with different base resistivity, were evaluated. The method of dopant diffusion with reduction of thermal steps is based on the patent required in INPI, developed in previous works. The sheet resistance in the phosphorus emitter increased with the increase of the boron diffusion temperature, used to form the back surface field. In the devices with low base resistivity (0.8 to 2.6 Ω.cm), the highest efficiency achieved with irradiance in the emitter (Emitter) and in the back surface field (BSF) was 16.0 % and 8.2% and was obtained with TB of 970 °C. In this solar cell, the bifaciality was 0.51 and the power output with bifacial mode was 17.6 mW/cm2 . These values were lower than those obtained with solar cells with higher base resistivity (1 to 20 Ω.cm). In this case, the Emitter was 16.3 % and the BSF was 10.2 %. Bifaciality and power output in bifacial mode were also slightly higher, of 0.63 and 18.3 mW/cm2 , respectively. These results were obtained with TB of 960 °C. The internal quantum efficiency (IQE) in the face with the back surface field was lower in all wavelengths and was affected by TB. In the face with the back surface field, the IQE of the solar cells with base resistivity of 1 to 20 Ω.cm was higher. We also found that in the face with the phosphorus emitter, the reflectance was affected by boron diffusion. The efficiency of the bifacial solar cells developed is slightly lower than that of commercial bifacial photovoltaic modules, but there are less steps in the production process.